Circulating sex hormones and breast cancer risk factors in postmenopausal women: reanalysis of 13 studies. - Key, T; Appleby, P; Reeves, G; Roddam, A; Helzlsouer, K; Alberg, A; Rollison, D; Dorgan, J; Brinton, L; Overvad, K; Kaaks, R; Trichopoulou, A; et al. (2011)
BACKGROUND: Breast cancer risk for postmenopausal women is positively associated with circulating concentrations of oestrogens and androgens, but the determinants of these hormones are not well understood. METHODS: Cross-sectional analyses of breast cancer risk factors and circulating hormone concentrations in more than 6000 postmenopausal women controls in 13 prospective studies. RESULTS: Concentrations of all hormones were lower in older than younger women, with the largest difference for dehydroepiandrosterone sulphate (DHEAS), whereas sex hormone-binding globulin (SHBG) was higher in the older women. Androgens were lower in women with bilateral ovariectomy than in naturally postmenopausal women, with the largest difference for free testosterone. All hormones were higher in obese than lean women, with the largest difference for free oestradiol, whereas SHBG was lower in obese women. Smokers of 15+ cigarettes per day had higher levels of all hormones than non-smokers, with the largest difference for testosterone. Drinkers of 20+ g alcohol per day had higher levels of all hormones, but lower SHBG, than non-drinkers, with the largest difference for DHEAS. Hormone concentrations were not strongly related to age at menarche, parity, age at first full-term pregnancy or family history of breast cancer. CONCLUSION: Sex hormone concentrations were strongly associated with several established or suspected risk factors for breast cancer, and may mediate the effects of these factors on breast cancer risk.